Cuban dental scientific production in the period 1995-2016: bibliometric analysis in Scopus - Ibraín Enrique Corrales-Reyes; Alberto Juan Dorta-Contreras (Editorial Ciencias Médicas, 2019)
Introduction: Bibliometric studies provide an interesting overview of the topic under analysis, thus attesting to its importance. Objective: To describe the Cuban scientific production ouput indexed in Scopus in the category Dentistry in the period 1995-2016. Methods: A search was conducted to identify publications indexed in Scopus under the category of dentistry in which at least one author was of Cuban professional affiliation. The bibliometric indicators of output, visibility and impact were addressed. Results: 518 papers were published (449 original), which have an h-index of 16 and have received 1 465 citations (207 self-citations). 2015 was the year when the largest number of papers was published (n= 51, 9.85 %). 53.86 % of the papers (n= 279) have been cited, and the average number of citations per document was 2.83. There was a predominance of papers published in Spanish in the Revista Cubana de Estomatología (n= 448, 86.49 %). In 15.64 % of the papers (n= 81) at least one author had been affiliated with the former Higher Institute of Medical Sciences of Havana, currently University of Medical Sciences of Havana. The most productive researcher was Daniele Botticelli, with 47 papers which have received 408 citations and have an h-index of 12. Conclusions: Cuban scientific production about dentistry exhibits a growing tendency characterized by the publication of original papers in Spanish in fourth quartile journals.